THE RELEVANCE OF ISLAMIC EDUCATION MANAGEMENT PRINCIPLES TO MODERN MANAGEMENT PARADIGMS: A LITERATURE STUDY IN THE CONTEXT OF INDONESIAN EDUCATION - Sofia Nur; Dwi Priyanto; Yulian Purnama (Review of International Journal Education and School Leadership, 2025)
This study aims to analyze the relevance of Islamic education management principles to modern management paradigms in the context of Indonesian education, employing a qualitative approach based on systematic literature reviews. Islamic management principles such as amanah, shura, 'adl, and ihsan were found to have a significant contribution in building school leadership that has integrity, participation, and is morally oriented. Literature analysis also shows that these values have a strong conceptual fit with modern management theories, including transformational leadership, distributed leadership, and value-based leadership. Despite the challenges of integration influenced by differences in normative and pragmatic orientations, the study's findings indicate that the two paradigms can be combined to form a hybrid leadership model that is relevant to the character of Indonesian education. This research makes a theoretical contribution by offering an integrative perspective that broadens the understanding of value-based leadership, while also opening up opportunities for more empirical and practical follow-up research. Practically, the results of this study provide strategic recommendations for school leaders, educational institutions, and policymakers on developing ethical, adaptive, and contextually relevant educational governance.